Elders’ quality of life. A method to optimize pedestrian accessibility to urban services. - Gaglione, Federica; Gargiulo, Carmela; Zucaro, Floriana (TeMA - Journal of Land Use, Mobility and Environment, 2019)
The progressive ageing of population requires rethinking the spatial planning of the urban spaces and activities to guarantee the best accessibility and usability to urban services of interest for the elderly segment of the population. In this perspective, the paper provides a methodology oriented to reorganize the urban services to better satisfy the renewed needs of over 65, by classifying the areas of a city according to (i) the levels of urban accessibility and (ii) the Functional Accessibility Soft zones (FASzones). In fact, the FASzones are the parts of the city where elderly can easily reach their services of interest due to the presence of "optimal" pedestrian routes fitting their behaviours. The results provide local decision-makers with useful suggestions for deciding where and how to in on the distribution and location of services, in order to increase urban accessibility for the over 65 by improving their quality of life. This methodological aim represents a first step in the broader MOBILAGE research work aimed at defining strategies, tools and actions to improve the pedestrian accessibility to urban services and places for elderly users.